Self-Management untuk Mengatasi Perilaku Prokrastinasi Akademik pada Peserta Didik: Studi Kepustakaan - Lulu Azzahra; Agus Tri Susilo; Citra Tectona Suryawati (Jurnal Psikoedukasi dan Konseling, 2022)
The purpose of the research is to identify the targets, procedures and successful implementation of self-management techniques to overcome the academic procrastination behaviour of students. The research method used is a literature study. The primary research data is 21 national and international articles. The article selection criteria are: meet both variables, carried out within the last ten years. Data collection techniques use documentation as well, as data analysis techniques using content analysis. The results of the study: (1) The targets were students who pursued formal education at the high school level who were identified as having behavioural problems with academic procrastination; (2) The implementation procedures in this study generally include self-monitoring, positive reinforcement, self-contracting, self-control, and follow-up;  and (3) the successful implementation of self-management to overcome academic procrastination behaviour in the form of a significant decrease in the level of academic procrastination. Based on 21 articles that researchers have analyzed, it shows that the achievement of the effectiveness of self-management in academic procrastination reaches 100%. Researchers are further advised to test the efficacy of self-management techniques to overcome academic procrastination behaviours for learners. Another piece of advice is to conduct research and development to produce self-management implementation guide products to overcome academic procrastination.